Body Integrity Identity Disorder and the Ethics of Mutilation - Song, Robert (Studies in Christian ethics, 2013)
The rare phenomenon in which a person desires amputation of a healthy limb, now often termed body integrity identity disorder, raises central questions for biomedical ethics. Standard bioethical discussions of surgical intervention in such cases fail to address the meaning of bodily integrity, which is intrinsic to a theological understanding of the goodness of the body. However, moral theological responses are liable to assume that such interventions necessarily represent an implicitly docetic manipulation of the body. Through detailed attention to the ethics of mutilation and of surgery for psychiatric disorders, this article explores the theological and ethical significance of the body for human identity.